The combined effects of fermentation and dehydration on the sensory quality of green papaya. - Tarranco, Desiree Dayuno (2014.)
The combined effects of fermentation and dehydration of mature, green papaya with total soluble solids (TSS) value of 5.44 was assessed in terms of sensorial qualities. The study was divided in three phases. Phase 1 involves the determination of the most acceptable fermentation period. The general acceptability of the green papaya with 5 days fermentation period and 2.5% salt solution was rated to be ?like moderately? by the ten (10) oriented panelists. Phase II was the dehydration of the most acceptable fermented papaya. The sample was dried for 2 hours at 700C. The product has a moisture content of 27.47%, water activity value of 0.668, residual salt content of 1.21% rehydration ratio of 6.88 and percent recovery value of 9.95%. Phase III was the conduct of sensory evaluation to determine the combined effects of fermentation and dehydration. A 7 point Hedonic Scale was used for rating the product. The Kruskal Wallis H-Test was used to analyse the responses of the panelists. It showed that the product has a distinct sour taste, fermented aroma, and saltiness while the dehydration process has provided for a firm mouthfeel or texture.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Papaya; Carica papaya; Fermentation; Sensory evaluation